PENGARUH HARGA DAN PROMOSI TERHADAP PROSES KEPUTUSAN PEMBELIAN ALAT KESEHATAN PADA PT BAHTERA SUKSES SEJAHTERA BSD TANGERANG SELATAN - Halawa, Jeniati; Senen (Journal of Research and Publication Innovation, 2024)
The purpose of this research is to determine the effect of price (X1) and promotion (X2) on purchasing decisions (Y) so with the title "The Influence of Price and Promotion on the Decision to Purchase Medical Devices (Case Study at PT Bahtera Sukses Sejahtera). The research method uses quantitative approach method which is associative with the population in this study which is 19.981 in purchasing decisions. The sample used in this study is a sampling technique with the technique taken, namely purposive sampling and using the Isaac Michael formula, a formula used to find a sample size that is considered capable of representing the entire population and using a Maximum Margin of Error of 0.10 or 10% so that a sample of 100 respondents was obtained. The partial price test results have a significant effect on purchasing decisions with t count > t table or (9.526 > 1.66055), This is also reinforced with a ρ value < Sig.0.05 or (0.000 < 0.05). The partial promotional test results have a significant effect on purchasing decisions with a calculated t value > t table or (14,327 > 1.66055). This is also reinforced by the ρ value < Sig.0.05 or (0.000 < 0.05). The results of testing prices and promotions simultaneously influence purchasing decisions with the calculated F value > F table or (117,030 > 3.09), this is also reinforced by the ρ value < Sig.0.05 or (0.000 < 0.05). Thus, Ho3 is rejected and Ha3 is accepted, this shows that there is a significant simultaneous influence between price (X1) and promotion (X2) on purchasing decisions (Y).